2021
DOI: 10.1111/jcmm.17018
|View full text |Cite
|
Sign up to set email alerts
|

Difference of immune cell infiltration between stable and unstable carotid artery atherosclerosis

Abstract: Atherosclerotic plaque instability contributes to ischaemic stroke and myocardial infarction. This study is to compare the abundance and difference of immune cell subtypes within unstable atherosclerotic tissues. CIBERSORT was used to speculate the proportions of 22 immune cell types based on a microarray of atherosclerotic carotid artery samples. R software was utilized to illustrate the bar plot, heat map and vioplot. The immune cell landscape in atherosclerosis was diverse, dominated by M2 macrophages, M0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
(77 reference statements)
0
20
0
Order By: Relevance
“…Previous studies have believed that atherosclerosis is caused by lipid deposition in the blood vessel wall, and as the study progresses [ 8 ]. It is gradually discovered that it is a chronic inflammatory disease of the arterial wall dominated by the aortic and middle arteries that is regulated by complex immune responses [ 9 ]. This chronic inflammatory response plays a key role in all stages of the atherosclerosis process, including atherosclerosis formation, progression, and plaque rupture eventually lead to thickening of the arterial wall lining, lumen narrowing, and even occlusion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have believed that atherosclerosis is caused by lipid deposition in the blood vessel wall, and as the study progresses [ 8 ]. It is gradually discovered that it is a chronic inflammatory disease of the arterial wall dominated by the aortic and middle arteries that is regulated by complex immune responses [ 9 ]. This chronic inflammatory response plays a key role in all stages of the atherosclerosis process, including atherosclerosis formation, progression, and plaque rupture eventually lead to thickening of the arterial wall lining, lumen narrowing, and even occlusion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that inflammatory macrophages and foam cell formation are crucial factors in atherosclerotic plague progression ( 44 , 45 ). T cells target the vessel wall in line with macrophages and react to antigens in the arterial wall ( 46 ). After activation of T cells, proinflammatory mediators are produced, exaggerating the inflammatory response, and disease development is worsened ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proportion of Infiltrating Immune Cells. The CIBER-SORT was a widely used method to assess the composition of immune cells in tumor microenvironment [20]. In our study, the CIBERSORT algorithm was used to evaluate the infiltration level of 22 immune cells in each BC sample.…”
Section: Survival Analysismentioning
confidence: 99%